Quantitative somatosensory assessments in patients with persistent pain following groin hernia repair: A systematic review with a meta-analytical approach. - Akhmedkhan Dubayev; Elisabeth Kjær Jensen; Kenneth Geving Andersen; Martin F Bjurström; Mads U Werner (PLoS ONE)
Objectives Quantitative sensory testing (QST) provides an assessment of cutaneous and deep tissue sensitivity and pain perception under normal and pathological settings. Approximately 2-4% of individuals undergoing groin hernia repair (GHR) develop severe persistent postsurgical pain (PPSP). The aims of this systematic review of PPSP-patients were (1) to retrieve and methodologically characterize the available QST literature and (2) to explore the role of QST in understanding mechanisms underlying PPSP following GHR. Methods A systematic literature search was conducted from JAN-1992 to SEP-2022 in PubMed, EMBASE, and Google Scholar. For inclusion, studies had to report at least one QST-modality in patients with PPSP. Risk of bias assessment of the studies was conducted utilizing the Newcastle Ottawa Scale and Cochrane's Risk of Bias assessment tool 2.0. The review provided both a qualitative and quantitative analysis of the results. A random effects model was used for meta-analysis. Results Twenty-five studies were included (5 randomized controlled trials, 20 non-randomized controlled trials). Overall, risk of bias was low. Compared with the contralateral side or controls, there were significant alterations in somatosensory function of the surgical site in PPSP-patients. Following thresholds were significantly increased: mechanical detection thresholds for punctate stimuli (mean difference (95% CI) 3.3 (1.6, 6.9) mN (P = 0.002)), warmth detection thresholds (3.2 (1.6, 4.7) °C (P = 0.0001)), cool detection thresholds (-3.2 (-4.9, -1.6) °C (P = 0.0001)), and heat pain thresholds (1.9 (1.1, 2.7) °C (P = 0.00001)). However, the pressure pain thresholds were significantly decreased (-76 (-123, -30) kPa (P = 0.001)). Conclusion Our review demonstrates a plethora of methods used regarding outcome assessments, data processing, and data interpretation. From a pathophysiological perspective, the most consistent findings were postsurgical cutaneous deafferentation and development of a pain generator in deeper connective tissues. Trial registration CRD42022331750.